2020
DOI: 10.1038/s42005-020-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

Superadiabatic demixing in nonequilibrium colloids

Abstract: Dispersed colloidal particles that are set into systematic motion by a controlled external field constitute excellent model systems for studying structure formation far from equilibrium. Here we identify a unique demixing force that arises from repulsive interparticle interactions in driven binary colloids. The corresponding demixing force density is resolved in space and in time and it counteracts diffusive currents which arise due to gradients of the local mixing entropy. We construct a power functional appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
(124 reference statements)
0
43
0
Order By: Relevance
“…In this context, it is relevant to note that Schmidt and co-workers have suggested that lane formation can be understood in terms of so-called superadiabatic forces, generated by the dynamics of a driven fluid. 49 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is relevant to note that Schmidt and co-workers have suggested that lane formation can be understood in terms of so-called superadiabatic forces, generated by the dynamics of a driven fluid. 49 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…The adiabatic construction was used to identify these superadiabatic force contributions. The concept of superadiabatic forces [31,32,44] allows systematic classification [42] of flow and structural effects, including viscous [39][40][41] and structural [41][42][43] force contributions. Future work could be directed at the behavior at low shear rates.…”
Section: Discussionmentioning
confidence: 99%
“…Functional integration methods were developed [38], and the relevance of local particle number conservation was demonstrated [56,57]. Expressing the superadiabatic free power functional via the velocity gradient [39][40][41][42][43] has facilitated the description of viscous [39,40,42] and of structural superadiabatic force contributions [41][42][43]. Superadiabatic forces are accessible in many-body simulations [32,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental systems of magnetic colloids that are placed above suitably patterned substrates offer much sophisticated control of driving protocols (Loehr et al, 2016(Loehr et al, , 2018. Geigenfeind et al (2020) have analyzed the forces that occur in the Brownian dynamics of a generic twodimensional binary repulsive sphere model. They recast the internal force density for binary mixtures (as laid out in Sec.…”
Section: Superdemixing and Laningmentioning
confidence: 99%
“…The dynamical DFT can be viewed as being based on the approximation that the nonequilibrium dynamics are represented as a sequence of "adiabatic states" that each are taken to be in equilibrium. While the adiabatic approximation for dynamical processes can be valid in certain cases, important physical effects are absent (Fortini et al, 2014), such as drag forces (Krinninger et al, 2016), viscosity (de las Heras and Schmidt, 2018), and structural nonequilibrium forces (de las Heras and Geigenfeind et al, 2020;Stuhlmüller et al, 2018;.…”
Section: Introduction a Soft Matter Dynamicsmentioning
confidence: 99%